Color evaporation description of inelastic photoproduction of J/ Ψ at DESY HERA - Éboli, O. J.P.; Gregores, E. M. [UNESP]; Halzen, F. (American Physical Society (APS), 2003)
The H1 Collaboration recently reported a new analysis of data on the inelastic photoproduction of J/Ψ mesons at DESY's HERA ep collider. We show that these new experimental results are well described by the color evaporation model for quarkonium production. Moreover, these new data require the introduction of resolved photon contributions in order to accommodate the results in the kinematic region where the fractional energy carried by the J/ Ψ is small, demonstrating that colored perturbative cc̄ states contribute to the production of a color singlet. © 2003 The American Physical Society.